PENGARUH GAYA HIDUP TERHADAP KEJADIAN DIABETES MELLITUS PADA PRA LANSIA DI RUMAH SAKIT UMUM DAERAH KOTA PADANGSIDIMPUAN - MARYAM LATIFAH HARAHAP (LP2MTBM MAKARIOZ, 2020)
The purpose of this study to analyze the influence of lifestyle (eating habits, physical activity and smoking) withincidence ofdiabetes meliitus in pre elderly in the General Hospital of the City Padangsidimpuan. The study used a case control study thepopulation of cases in this study were all pre elderly people aged 45-59 years who suffered diabetes mellitus. The populationcontrol is a pre elderly people aged 45-59 years who do not have diabetes mellitus as many as 45 people. Data werecollected through medical records and interviews used questionnaires. Data was analyzed by univarite, bivariate, used Chi-Square test at the level of 95% (P <0,05) and multivariate used multiple logistic regression. The results of this studyshowedthat the statistical test results of the independent variable of eating habits acquired Sig value 0.000 <p: 0. Physicalactivity obtained Sig value 0.001 <p: 0.05 Smoking habits acquired Sig value 0.001 <p: 0.05 means there is a significantrelationship with the dependent variable independent. Variables that affect the incidence of diabetes mellitus that physicalactivity and eating habits, with a value of p <0.05. The most dominant variable having the most influence on the incidence ofdiabetes mellitus is a physical activity has a value of Exp (B) most is 112.687 with a regression coefficient (B) 4,725. It isexpected to Padangsidimpuan general hospital to enhance the role of health workers in particular to disseminate scientificinformation about diabetes mellitus involving health workers, community leaders and religious leaders.